Pengembangan LKPD Berbasis Deep Learning Dalam Pembelajaran Matematika Untuk Meningkatkan Motivasi Belajar Siswa Kelas IIID SD Islam Khaira Ummah - Nesza; Dini Susanti (PT Suria Academic Press, 2026)
This research was motivated by the low learning motivation of Grade III D students at SD Islam Khaira Ummah in mathematics, particularly in the topic of whole number division. This condition was caused by the use of worksheets (LKPD) that were less varied, less interactive, and had not encouraged students to think deeply. Therefore, this study aimed to develop a Deep Learning–Based LKPD in mathematics learning to improve students’ learning motivation that meets the criteria of validity, practicality, and effectiveness.This study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The LKPD was developed using a Deep Learning approach and implemented through the Discovery Learning model. The validity test was conducted by material, language, and design experts. Practicality was assessed by the classroom teacher, while effectiveness was measured through a learning motivation questionnaire and pre-test and post-test results involving 25 students.The results showed that the developed LKPD achieved a validity level of 89% (very valid), practicality of 97% (very practical), and effectiveness of 90% (very effective). Thus, the LKPD is feasible to enhance students’ motivation in mathematics learning.